2016
DOI: 10.1002/micr.30086
|View full text |Cite
|
Sign up to set email alerts
|

Free anterolateral thigh flap and masseter nerve transfer for reconstruction of extensive periauricular defects: Surgical technique and clinical outcomes

Abstract: Extensive periauricular defects following oncologic resection could be adequately reconstructed in a combined procedure of free ALT flap and masseter nerve transfer to the facial nerve for smile restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…-Flap Selection: Composite defects in the periauricular area can be successfully reconstructed with the ALT flap. It is a versatile flap that can be tailored to the needs of the defect designed as fasciocutaneous, adipofascial, or chimeric flap (Elliott et al 2011;Cristóbal et al 2017;Maldonado et al 2017).…”
Section: Avoiding and Managing Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…-Flap Selection: Composite defects in the periauricular area can be successfully reconstructed with the ALT flap. It is a versatile flap that can be tailored to the needs of the defect designed as fasciocutaneous, adipofascial, or chimeric flap (Elliott et al 2011;Cristóbal et al 2017;Maldonado et al 2017).…”
Section: Avoiding and Managing Problemsmentioning
confidence: 99%
“…Start with the medial incision during Intraoperative image after nerve reconstruction with the masseter nerve transfer to the buccal and zygomatic branches and the facial nerve stump with a nerve graft to the frontal and temporal branches. (Reused with permission from Cristóbal et al 2017) the ALT harvest. Do not complete lateral incision of the skin paddle until the oncological resection has finished and the template has been designed.…”
Section: Avoiding and Managing Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Nerve transfers, meanwhile, provide a source of healthy axons that may be used for coaptation with the damaged facial nerve. 44 The masseter nerve has recently increased in popularity as the donor nerve for facial nerve reconstruction due to its consistent anatomy, strength of motor impulses, and fast recovery of muscle tone and motion. The masseter nerve transfer is also associated with very low donor-site morbidity, which makes it an ideal choice for the treatment of both small and large facial defects.…”
Section: Facial Reconstructionmentioning
confidence: 99%
“…Furthermore, recent advances in free tissue transfer have facilitated correction of periauricular defects. The use of an anterolateral thigh flap in combination with masseteric nerve transfer has been described by Cristóbal et al 33 in a case series of 6 patients to improve contour deformity and facial nerve function. The authors observed adequate volume replacement and restored facial symmetry, with no partial or total flap loss.…”
Section: Frontiers In Facial Reconstructionmentioning
confidence: 99%